2021
DOI: 10.1155/2021/8243378
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Extracellular Matrix and Neutrophils in Diseases

Abstract: The extracellular matrix (ECM) is a highly dynamic and complex network structure, which exists in almost all tissues and is the microenvironment that cells rely on for survival. ECM interacts with cells to regulate diverse functions, including differentiation, proliferation, and migration. Neutrophils are the most abundant immune cells in circulation and play key roles in orchestrating a complex series of events during inflammation. Neutrophils can also mediate ECM remodeling by providing specific matrix-remod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 105 publications
0
37
0
Order By: Relevance
“…There is mounting evidence of complex interactions between ECM macromolecules and PMN (reviewed recently by Zhu et al). We now know that the close relationship between ECM and PMNs plays an important role in the progression of various diseases in humans ( 205 ). Recent studies for example demonstrated an important role for ECM in fighting against infectious diseases by mediating an antifungal response of PMNs ( 205 207 ).…”
Section: Current Knowledge and Controversies Of The Influence Of The Extra-cellular Matrix On The Function Of Neutrophilsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is mounting evidence of complex interactions between ECM macromolecules and PMN (reviewed recently by Zhu et al). We now know that the close relationship between ECM and PMNs plays an important role in the progression of various diseases in humans ( 205 ). Recent studies for example demonstrated an important role for ECM in fighting against infectious diseases by mediating an antifungal response of PMNs ( 205 207 ).…”
Section: Current Knowledge and Controversies Of The Influence Of The Extra-cellular Matrix On The Function Of Neutrophilsmentioning
confidence: 99%
“…We now know that the close relationship between ECM and PMNs plays an important role in the progression of various diseases in humans ( 205 ). Recent studies for example demonstrated an important role for ECM in fighting against infectious diseases by mediating an antifungal response of PMNs ( 205 207 ). Moreover, experimental studies have shown that released NETs cleave fibronectin via NE and MMP-9 to further degrade ECM in alveoli, thereby promoting the development of bronchopulmonary dysplasia ( 205 , 208 ).…”
Section: Current Knowledge and Controversies Of The Influence Of The Extra-cellular Matrix On The Function Of Neutrophilsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through their whole battery of membrane receptors and secretory molecules they communicate with other immune cells to elicit co-operating immune responses for combating the invaders. In addition, they interact with both endothelial and epithelial cells and the extracellular matrix that enable their migration into and through the tissues [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%